Early Prediction of Malignant Cerebellar Edema in Posterior Circulation Stroke Using Quantitative Lesion Water Uptake. Issue 3 (10th October 2020) - Broocks, Gabriel; Elsayed, Sarah; Kniep, Helge; Kemmling, Andre; Flottmann, Fabian; Bechstein, Matthias; Faizy, Tobias D; Meyer, Lukas; Lindner, Thomas; Sporns, Peter; Rusche, Thilo; Schön, Gerhard; et al.
Abstract: BACKGROUND: Malignant cerebellar edema (MCE) is a life-threatening complication of ischemic posterior circulation stroke that requires timely diagnosis and management. Yet, there is no established imaging biomarker that may serve as predictor of MCE. Early edematous water uptake can be determined using quantitative lesion water uptake, but this biomarker has only been applied in anterior circulation strokes. OBJECTIVE: To test the hypothesis that lesion water uptake in early posterior circulation stroke predicts MCE. METHODS: A total 179 patients with posterior circulation stroke and multimodal admission CT were included. A total of 35 (19.5%) patients developed MCE defined by using an established 10-point scale in follow-up CT, of which ≥4 points are considered malignant. Posterior circulation net water uptake (pcNWU) was quantified in admission CT based on CT densitometry and compared with posterior circulation Acute Stroke Prognosis Early CT Score (pc-ASPECTS) as predictor of MCE using receiver operating curve (ROC) analysis and logistic regression analysis. RESULTS: Acute pcNWU within the early ischemic lesion was 24.6% (±8.4) for malignant and 7.2% (±7.4) for nonmalignant infarctions, respectively ( P < .0001). Based on ROC analysis, pcNWU above 14.9% identified MCE with high discriminative power (area under the curve: 0.94; 95% CI: 0.89-0.97). Early pcNWU (odds ratio [OR]: 1.28; 95% CI: 1.15-1.42, P < .0001) and pc-ASPECTS (OR: 0.71, 95% CI: 0.53-0.95, P = .02) were associated with MCE, adjusted for age and recanalization status. CONCLUSION: Quantitative pcNWU in early posterior circulation stroke is an important marker for MCE. Besides pc-ASPECTS, lesion water uptake measurements may further support identifying patients at risk for MCE at an early stage indicating stricter monitoring and consideration for further therapeutic measures.